2022
DOI: 10.1590/fst.40421
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the structure, biological activity and molecular mechanisms of polysaccharides from Craterellus cornucopioide (CC-M) and Dictyophora indusiata (Vent.ex Pers) Fisch (DI-Z)

Abstract: In this study, two new polysaccharides were extracted from the fruiting bodies of Craterellus cornucopioide and Dictyophora indusiata (Vent.ex Pers) Fisch, respectively. The results showed that CC-M was composed of Xyl: Glc: Gal in a ratio of 2:5:4. The CC-M takes 1,6-glucose and 1,6-galactose as skeletons, extends a branched chain from galactose 2-O to connect 1,3,4-xylose, and connects β-4-glucose terminal monosaccharide to xylose. DI-Z was also composed of Xyl: Glc: Gal in the ratio of 2:6:5, which takes 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…They have the ability to stimulate the functioning of the immune system in mice by stimulating the activity of RAW264.7 macrophages. Ding et al [60] came to similar conclusions as a result of examining the bioactivity of the CC-M polysaccharide isolated from C. cornucopioides. It increased the activity of T and B lymphocytes and RAW264.7 macrocytes and stimulated the signaling pathways of MAPK, PI3K-Akt, NF-κB, and NOD-like receptor signaling pathway receptors as a result of stimulating the secretion of CD163, IL-1β, IL-6, IL-10, and TNF-α.…”
Section: Immunostimulating and Anti-inflammatory Effectsmentioning
confidence: 63%
“…They have the ability to stimulate the functioning of the immune system in mice by stimulating the activity of RAW264.7 macrophages. Ding et al [60] came to similar conclusions as a result of examining the bioactivity of the CC-M polysaccharide isolated from C. cornucopioides. It increased the activity of T and B lymphocytes and RAW264.7 macrocytes and stimulated the signaling pathways of MAPK, PI3K-Akt, NF-κB, and NOD-like receptor signaling pathway receptors as a result of stimulating the secretion of CD163, IL-1β, IL-6, IL-10, and TNF-α.…”
Section: Immunostimulating and Anti-inflammatory Effectsmentioning
confidence: 63%
“…Studies also have shown that there are certain differences in the amount and structural characteristics of polysaccharides contained in different edible fungi (Jing et al, 2021). For example, Craterellus cornucopioide polysaccharides and Dictyophora indusiata (Vent.ex Pers) Fisch polysaccharides with similar monosaccharide composition had proliferative activity on specific immune cells such as B cells, T cells and RAW264.7 cells, but Craterellus cornucopioide polysaccharides had a better effect on immune cell proliferation than Dictyophora indusiata (Vent.ex Pers) Fisch polysaccharides (Ding et al, 2022b). The molecular weight of polysaccharides affects the biological activity of polysaccharides.…”
Section: Active Structure Of Edible Fungus Polysaccharidesmentioning
confidence: 99%
“…26 In a different study on C. cornucopioides polysaccharide extract, the monosaccharide composition was detected as xylose: glucose: galactose with a 2:5:4 molar ratio. 27 2.3. FT-IR Analysis.…”
Section: Monosaccharide Compositionmentioning
confidence: 99%